تقويم سياسة رفع قيمة الدينار العراقي مقابل الدولار الأمريكي (المجلة العراقية للعلوم الاقتصادية, 2018)
the monetary authority in Iraq has realized a noticeable decline in inflation rates over the period 2007-2010 . this remarkable achievement is due to lasting efforts made by this authority , mainly through a permanent intervention of the Iraqi central bank in the foreign exchange market . the official intervention consists in selling foreign exchange (dollars) and buying domestic currency (dinars) with purpose of withdrawing part of money supply and raising the value of dinars VS dollars .A significant appreciation in the nominal exchange rate of domestic currency can help to decrease the price of imported goods and services and lead to dampen imported inflation .However, the actions of monetary authority seeking to push up the nominal nation's currency don't necessarily accord with economic fundamentals . in other word , this action puts emphatically upward pressure on the domestic currency or downward pressure on the foreign currency . in responding to continuous strategy to depreciate the foreign currency (dollars) in the official market , there has been not only movement in the exchange rate of the domestic currency in undesirable level but also an excessive demand on the foreign currency from the market players , specially banks and speculators which result in an important depreciation in the value of the nation's currency along with high inflation rate